2019
DOI: 10.1103/physrevd.100.114019
|View full text |Cite
|
Sign up to set email alerts
|

Heavy quark diffusion in a Polyakov loop plasma

Abstract: We calculate the transport coefficients, drag and momentum diffusion, of a heavy quark in a thermalized plasma of light quarks in the background of Polyakov loop. Quark thermal mass and the gluon Debye mass are calculated in a non-trivial Polyakov loop background. The constituent quark masses and the Polyakov loop is estimated within a Polyakov loop quark meson (PQM) model. The relavant scattering amplitudes for heavy quark and light partons in the background of Polyakov loop has been estimated within the matr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…For all cases, a markedly different feature from the standard pQCD approach are the rather large thermal-parton masses dictated by the constraints from the QGP EoS and microscopically related to the Polyakov loop encoding the nontrivial information of the confinement [36] JHEP08(2020)168 generated selfconsistently from the confining potential. Similar features from including effects of the Polyakov loop have recently been found from a different perspective, within the Polyakov-quark-meson model [47]. With a gluon mass of around 1 GeV at low temperature, soft radiation is heavily suppressed.…”
Section: Spectral Properties Of Radiated Partonssupporting
confidence: 72%
“…For all cases, a markedly different feature from the standard pQCD approach are the rather large thermal-parton masses dictated by the constraints from the QGP EoS and microscopically related to the Polyakov loop encoding the nontrivial information of the confinement [36] JHEP08(2020)168 generated selfconsistently from the confining potential. Similar features from including effects of the Polyakov loop have recently been found from a different perspective, within the Polyakov-quark-meson model [47]. With a gluon mass of around 1 GeV at low temperature, soft radiation is heavily suppressed.…”
Section: Spectral Properties Of Radiated Partonssupporting
confidence: 72%
“…We have taken q = 1.01, and temperature to be 350 MeV (for Figs. 5,7,9), and momentum of the energetic light quark to be 5 GeV (for Figs. 6,8,10).…”
Section: A Nebte In the Rtamentioning
confidence: 99%
“…Since then, it has been used in many fields including that of high energy collisions. For example, to understand the transport of particles inside the quark-gluon plasma medium produced in high energy collisions, either the BTE, or some approximated version of it has been used [2][3][4][5][6][7][8]. In this approach, the evolution of a distribution function is studied, and is utilized to understand the observables in the multi-particle production experiments colliding protons or heavy-ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, this has been attempted with the relax-ation time estimated within perturbative QCD which may be valid for asymptotically high temperatures. Further, it ought to be mentioned that, the vacuum structure of QCD remain nontrivial near the critical temperature region with nonvanishing values for the quark-antiquark condensates associated with chiral symmetry breaking as well as Polyakov loop condensates associated with the physics of statistical confinement [77][78][79][80]. Indeed, within the ambit of the NJL model, it was shown that the temperature dependence of viscosity coefficients exhibits interesting behavior of phase transition with the shear viscosity to entropy ratio showing a minimum while the coefficient of bulk viscosity showing a maximum at the phase transition [77,78,81].…”
Section: Introductionmentioning
confidence: 99%